The Effects of CTL And PjBL Models Assisted by Diorama Media on Students’ Creative Thinking Abilities - Nurul Aeni; Sintayana Muhardini; Syafruddin Muhdar (MIMBAR PGSD Undiksha, 2024)
Education is a key factor in improving individuals' quality of life and thinking abilities. However, there are still many challenges in implementing effective learning models, especially at the elementary school level. This study aims to explore and compare the influence of the Contextual Teaching and Learning (CTL) model and the Project-Based Learning (PjBL) model, supported by diorama media, on students' creative thinking abilities. This research employed an experimental method with a quasi-experimental nonequivalent control group design, involving 44 fourth-grade elementary school students, divided into Class IVA (21 students) and Class IVB (23 students). Data were collected through essay tests consisting of 10 questions about animal life cycles. The research instruments included question sheets and observation sheets. Data analysis was conducted using descriptive and inferential statistics, including normality tests, variance homogeneity tests, and t-tests. The results showed that the PjBL model was more effective in improving creative thinking skills, with an average score of 75.86 compared to CTL, which only reached 67.14. This study concludes that implementing the PjBL model with the support of diorama media can enrich the learning experience and stimulate students' creativity. The implication of this interactive and collaborative learning model is an increase in student engagement and motivation in the learning process.